Variability in the Relationship Between Sleep and Pain in Patients Undergoing Interdisciplinary Rehabilitation for Chronic Pain. Issue 6 (9th April 2014) - Davin, Sara; Wilt, Josh; Covington, Edward; Scheman, Judith
Abstract Objective Chronic pain and sleep disturbance frequently coexist and often complicate the course of treatment. Despite the well‐established comorbidity, there are no studies that have investigated concurrent changes in sleep and pain among patients participating in an interdisciplinary chronic pain rehabilitation program (ICPRP). The goal of this study was to investigate the daily changes in sleep and pain among patients participating in an ICPRP. Methods Multilevel modeling techniques were used to evaluate the daily changes in total sleep time (TST) and pain among a sample of 50 patients with chronic noncancer pain participating in the ICPRP. Results Increases in TST were predictive of less pain the following treatment day, although daily pain ratings were not predictive of that night's TST. Time in treatment was a significant predictor of both TST and pain reduction, even while controlling for age, gender, anxiety, and depression. Additional analyses revealed significant individual variability in the relationship between TST and next day pain. Individuals with stronger associations between previous night's TST and next day pain were found to experience the greatest treatment benefits overall, in terms of pain reduction and TST. Conclusions Our results provide compelling support for individual variability of the pain–sleep relationship in patients with intractable pain conditions participating in an ICPRP. Importantly, these findings suggest that when pain and sleep are comorbid, both must be addressed to reap the maximum response to treatment programs such as an ICPRP. Perspective Statement This study demonstrates the utility of treating sleep problems in patients participating in an interdisciplinary chronic pain rehabilitation program. Results highlight the benefits of accounting for individual variability in the pain‐sleep relationship in a clinical setting and targeting sleep interventions for those individuals whose pain and sleep problems are comorbid.